KINERJA PELAYANAN PUBLIK DI RAWAT INAP RUMAH SAKIT UMUM DAERAH UNDATA PALU PROVINSI SULAWESI TENGAH - Rizki, Mohamad; Suasa; Nurhannis (Berajah Journal, 2025)
This research aims to determine the performance of Public Services in the Inpatient of Undata Palu Hospital, Central Sulawesi Province, a type of research using descriptive research. Meanwhile, the basis of the research is qualitative. This study used 5 (five) informants, including 1 (one) doctor, 2 (two) health workers, and 2 (two) public (patients). This research uses the theory of Agus Dwiyanto, which is based on 5 (five) indicators, namely, Productivity, Service Quality, Responsiveness, Responsibility, and Accountability. This research is carried out with 3 (Three) data collection techniques, namely, observational literature studies, interviews, and documentation. Based on the results of the research obtained by the author, the author draws the conclusion that the level of performance of Inpatient Public Services at Undata Palu Hospital, Central Sulawesi Province is quite good, judging from the level of Productivity, Responsibility, and Accountability which is quite good, while judging from the Responsiveness and Service Quality are still lacking or not good enough.